Cecal Endometriosis Presenting as Acute Appendicitis - Hamidreza Alizadeh Otaghvar; Mostafa Hosseini; Ghazaal Shabestanipour; Adnan Tizmaghz; Gandom Sedehi Esfahani (Case Reports in Surgery)
The aim of our paper is to show the diagnosis of Coecal endometriosis as an infrequent reason of right iliac fossa pain. cecal endometriosis manifesting with right lower quadrant pain is difficult to diagnose, and it may even sometimes require laparotomy for diagnosis and treatment. We report here a case of cecal endometriosis causing clinically resembled acute appendicitis. In our patient, a diagnosis of cecal endometriosis was made postoperatively by microscopic examination of excised right colon, and the patient symptoms and general condition were improved after the surgery (open right hemicolectomy and ileocolic anastomosis).